NANOSTRUCTURAL PROCESSES OF MELTING AND CASTING OF CAST IRON WITH FLAKY GRAPHITE - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия, 2017)
It is shown that melting and casting of cast iron with flaky graphite are the complex physical and chemical nanostructural processes. The majorrole in these processis played by the centers of crystallization of dendrites of graphite, graphite nanocrystals, the dissolved and adsorbed oxygen. The modifying ligature of FS75 is used to decrease concentration of the adsorbed oxygen and to fusion enrichment by the centers of crystallization of dendrites of graphite.